What causes energy and transport poverty in Ireland? Analysing demographic, economic, and social dynamics, and policy implications - Lowans, Christopher (2022)
Energy and transport poverty have been postulated as conditions linked by overlapping causal factors such as structural economic inequality or housing stock and affecting overlapping demographics such as family size or income. The strength of the overlap of these conditions and their causal mechanisms has not been assessed across Ireland prior to this study. We apply and analyse existing and novel energy and transport poverty metrics in a survey of 1564 participants across Ireland and consider results from expenditure and consensual data examining causal mechanisms and correlations. We find that energy and transport poverty rates are broadly similar across Ireland at approximately 14% for energy poverty and 18% for transport poverty using the half-median metric, while participant knowledge of causal factors, such as lack of domestic energy efficiency and perceived desirability of potential poverty solutions, such as increased public transport provision, are low. Furthermore, we find that self-reported data concerning energy and transport expenditures and preferences do not correspond to expected outcomes. We thus conclude that ever refined targeting of individuals and households for support measures is not optimal for either decarbonisation or alleviation of energy and transport poverty conditions and suggest some salient policy implications.